Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025746
|View full text |Cite
|
Sign up to set email alerts
|

Five Lenses for Designing Exertion Experiences

Abstract: The field of HCI has increasingly looked at ways to support the physically active human being, however, new work suggests that the field has only begun to understand the many virtues of exertion. To further the field, we present a set of five design lenses extended primarily from sports philosophy literature to help approach exertion not just as a means of deferring death, but also as an opportunity for personal growth. The lenses facilitate learning how to appreciate a void (Reverie), welcome pleasure (Pleasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 72 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…The experiential lenses are concerned with the visceral aspects that unfold throughout the jogging experience, whereas the instrumental lenses are aimed to provide an underlying structure to support the jog. The experience-focused view on jogging aligns with current popular jogging culture accounts [44] that recommend shifting our perspective of seeing jogging as a task to be accomplished (such as when doctors prescribe physical activity) to seeing jogging as an opportunity to facilitate personal growth [3,83]. By considering the instrumental lenses, designers can support the "mechanics" of jogging.…”
Section: The Jogging Lensesmentioning
confidence: 88%
See 1 more Smart Citation
“…The experiential lenses are concerned with the visceral aspects that unfold throughout the jogging experience, whereas the instrumental lenses are aimed to provide an underlying structure to support the jog. The experience-focused view on jogging aligns with current popular jogging culture accounts [44] that recommend shifting our perspective of seeing jogging as a task to be accomplished (such as when doctors prescribe physical activity) to seeing jogging as an opportunity to facilitate personal growth [3,83]. By considering the instrumental lenses, designers can support the "mechanics" of jogging.…”
Section: The Jogging Lensesmentioning
confidence: 88%
“…Designing for jogging can also learn from perspectives of being physically active. For example, several movementfocused research projects [23,34,36,45,72,83] highlight the expressive power of bodily movement and its potential in a public context. These works led us to lenses that consider the larger public space, such as jogging in a park.…”
Section: Related Workmentioning
confidence: 99%
“…Participants also observed that two lines of conversations emerged when reflecting on the activity; one was about designing for the human body from the lens of what is good for the human, while the second line is about designing new experiences that are experiential and not necessarily good for the human body; however, they do not necessarily need to stand in contrast, as Mueller and Young previously highlighted [3].…”
Section: One Of the Design Outcomesmentioning
confidence: 99%
“…Moving the body comes with certain risks, however, these risks have value in and of themselves, and interaction designers need to be aware of how to deal with this [3]. Participants argued that the alternative is to design for stillness, which might not facilitate immediate injury, but ultimately leads to obesity and unhappiness, something that all participants aimed to avoid.…”
Section: Open Questions Around Body-centric Computingmentioning
confidence: 99%
“…That is, these systems should empower users with knowledge about their body, and facilitate improving skills through training and practice (Doherty, Lemieux, & Canally, 2014). To address this, the systems should facilitate listening to the "inside" of their body and should give reasonable feedback rather than simply forcing the users to push their limits (Mueller & Young, 2017).…”
Section: Challenges Of Designing For Active Exercisersmentioning
confidence: 99%